Pengaruh Ekonomi Hijau dan Kepemilikan Manajerial Terhadap Pengembalian Saham Masa Depan dan Persistensi Laba dengan Volume Perdagangan sebagai Pemoderasi - Celia Darmasaputra; Nera Marinda Machdar (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This research aims to show the influence of green economy and managerial ownership to future returns stock and earnings persistence with and without volume trading stock as moderator. The sample used in this research are 55 manufacturing companies listed in Indonesia Stock Exchange (IDX) in 2013-2018. This research uses the method of data analysis with 2 regression models, the method is multiple regression analysis and moderated regression analysis (MRA), the data processed using Eviews 9. The results of this study shows that: (a) green economy has negative significant effect to future returns stock; (b) green economy has no significant effect to earnings persistence; (c) managerial ownership has no significant effect to future returns stock; (d) managerial ownership has no significant effect to earnings persistence; (e) volume trading stock does not moderate the effect of green economy and managerial ownership to future returns stock; and (f) volume trading stock does moderate the effect of green economy and managerial ownership to earnigs persistence.